The Acelerating Effect of Fibrinogen and Early Fibrinogen Degradation Products on Erythrocyte Sedimentation - Marsh, N A (Thrombosis and Haemostasis, 1979)
The fibrinogen molecule has a number of biological activities and some of these are shared by the larger degradation products. This study was carried out to investigate the erythrocyte sedimentation-accelerating property of fibrinogen and how this property might be modified by proteolytic digestion with plasmin.The sedimentation rate of washed human red cells suspended in saline, was found to be directly proportional to the concentration of added purified human fibrinogen, down to 250 mg%, below which there was no difference from saline controls. Plasmic digestion of fibrinogen yielding fragment X, did not reduce the accelerating affect on erythrocyte sedimentation, indicating that the intact carboxyl terminal end of the Aα chain is unnecessary for this phenomenon. Further digestion to fragment Y reduced the effect slightly but digestion to fragments D and E abolished the accelerating effect completely.